PEMBENTUKAN KARAKTER RELIGIUS DAN SOSIAL SISWA MELALUI EKSTRA KULIKULER ALBANJARI DI MTS NU SUKODADI - Muhammad Fadllu Maulana Putra; Ida Latifatul Umroh; Intan Ayu (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This article aims to comprehensively examine the influence of Al-Banjari extracurricular activities on the formation of religious and social character of students at MTs Ma'arif NU Sukodadi. Using a qualitative method with a case study approach, it aims to gain an in-depth understanding of the phenomena of behaviour, perceptions, motivations, and actions of the research subjects in their natural context. The results of the study show that with the Al-Banjari extracurricular activities, students' religious character can be formed,  1) students have religious character 2) students have a high level of piety 3) students have a high level of spirituality 4) students have a love for the Prophet Muhammad SAW, 5) students have a high level of discipline, and the social character of students includes 1) students have good character or ethics towards others 2) students can establish solidarity among fellow students 3) students have a great sense of responsibility 4) students have a high spirit of mutual cooperation 5) students have a high spirit of creativity.